A expressividade do professor universitário em situação experimental e de interação em sala de aula - Tania Afonso Chaves (2009)
The main purpose of the present research was analyzing the expressiveness strategies of university teachers, concerning paraverbal and non-verbal resources. That interdisciplinary study aims to describe and correlate the different dimensions of those resources to their linguistic and pragmatic meaning, without leaving behind each professors emotional dimensions and communicative style. Subjacent motivations to that work are the need to contribute to Education in professors formation and also to Speech Therapy, indicating that the study on the teachers expressiveness must contemplate the several dimension of the communicative act e can be much more broad than that being developed and which many times is limited specifically to voice caring. The theoretical premises adopted come from three trends. Concerning the class and the work carried by the teacher, we made use of authors that approach the theme of superior education. To analyzing the expressiveness strategies, we have applied concepts fro the study on paraverbal and non-verbal resources. And, finally, in relation to the communication in class, we followed the trend of social interactionism, in special the concepts of interaction, context, episodes, and the tool for video analyses. The methodology we have adopted consisted in observations, exams, questionnaires and video recording of authentic class situations. The data analyze was carried out in two different moments macro and micro. The analyses methods was of quantitative and qualitative nature, with a set of categories previously delimited, according to the theoretical premises adopted, categories to which others were added during the analyses. To analyzing the strategies of paraverbal expressiveness were used variations of pitch, intensity and fluency, related to six basic emotions, as well as articulations between those data and the docents profile. To characterize the non-verbal expressiveness of the university teacher, we have considered the aspects of gestures and face expressions. The evaluation and investigation of the perception both from the students and teachers were carried out using TCBQ. And, finally, in relation to expressiveness and class practices, the teachers studied in the research were videotaped and their classes were analyzed through the categories system proposed by Mortimer et al (2005). The results found show that it is needed to get to know the expressiveness resources used by the teachers, and how those resources circulate in the class. It is possible to delimitate the characteristics of paraverbal and non-verbal resources e their use according to the professors style, and, also, to observe that is indispensable to include a new dimension for analyses and diagnosis, that can serve as a strategy for action on the qualification of professors in their work.